2020
DOI: 10.3168/jds.2019-18068
|View full text |Cite
|
Sign up to set email alerts
|

Negative dietary cation-anion difference and amount of calcium in prepartum diets: Effects on milk production, blood calcium, and health

Abstract: Acidogenic prepartum diets with negative dietary cation-anion difference (DCAD) induce compensated metabolic acidosis, which stimulates calcium (Ca) mobilization before calving and decreases clinical and subclinical hypocalcemia postpartum. This strategy is often combined with limiting dietary Ca concentrations, which historically has been used to mobilize Ca prepartum to prepare cows for lactation. Supplemental dietary Ca in combination with a negative DCAD formulation that does not reverse the effect of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 46 publications
3
23
1
1
Order By: Relevance
“…Additionally, Amundson et al (2018) demonstrated that feeding a low DCAD diet with high dietary Ca increased the amount of EGTA required to place cows in a state of SCH, suggesting an increased amount of rapidly available Ca in cows fed a low DCAD, high Ca diet. Recently, we (Glosson et al, 2020) reported little effect of high Ca supplementation in a negative DCAD diet on blood Ca concentration or production of Holstein cows, but their reproductive performance including uterine health and fertility was improved by the higher dietary Ca (Ryan et al, 2020). How the blood acid-base balance system and metabolism around parturition respond to a negative DCAD diet with or without supplemental dietary Ca is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Amundson et al (2018) demonstrated that feeding a low DCAD diet with high dietary Ca increased the amount of EGTA required to place cows in a state of SCH, suggesting an increased amount of rapidly available Ca in cows fed a low DCAD, high Ca diet. Recently, we (Glosson et al, 2020) reported little effect of high Ca supplementation in a negative DCAD diet on blood Ca concentration or production of Holstein cows, but their reproductive performance including uterine health and fertility was improved by the higher dietary Ca (Ryan et al, 2020). How the blood acid-base balance system and metabolism around parturition respond to a negative DCAD diet with or without supplemental dietary Ca is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Glosson et al. (2020) showed that increasing the Ca content from 0.44% to 1.97% by adding limestone did not affect DMI. As sorting behaviour was not altered, differences in palatability between the HCLK and the LCLK diets in palatability seem unlikely, but cannot be excluded.…”
Section: Discussionmentioning
confidence: 89%
“…Following an approach similar to that of Weiss and Wyatt (2000), we performed an a posteriori power calculation based on the variance in DMI observed in this study and concluded that a sample size of 32 cows per treatment would have been necessary to make the 2.4-kg/d difference statistically different with an 0.80 statistical power at a 0.05 significance level. Compared to other studies (Goff and Koszewski, 2018;Lopera et al, 2018;Glosson et al, 2020), we acknowledge the limited sample size of our study to detect a 2.4-kg/d difference on DMI with an 0.80 statistical power at a 0.05 significance level. In regard to polyhalite, DMI during the prepartum period of cows consuming the NEG diet differed numerically, but not statistically (P = 0.80), by 0.9 kg/d less than DMI of cows consuming the CON diet.…”
Section: Es Richardson Et Almentioning
confidence: 81%